Production Of Biogas By Using Air Stripping As Pre-Treatment Process In Anaerobic Digestion Of Palm Oil Mill Effluent (POME) - Farhana, Zaimustafa (2022)
This study aims to produce biogas from palm oil mill effluent in anaerobic digestion through the pre-treatment of the air stripping process. Air stripping is the process of moving air through contaminated water with volatile contaminants in a treatment system above ground. The air movement process causes volatiles to evaporate at a faster rate. Ammonia stripping is a cost-effective technique that requires little energy inputs and involves the transfer of free ammonia from wastewater to the gas phase. High removal of ammonia nitrogen helps in enhancing biogas production through anaerobic digestion while anaerobic digestion is a process which bacteria break down organic matter in the absence of oxygen to produce biogas. It is an environmentally friendly method for treating and recovering bioenergy from a variety of organic wastes. In this study, raw POME will be tested for its, ammonia nitrogen content and changing the pH content of raw POME from acidic 4.17 to alkaline 8. Then, two bottles of 550ml POME are filled in the glass bottle to undergo the air stripping pre-treatment process. One of the bottles will undergo an air stripping pre-treatment process while another glass bottle will be used as a control for an anaerobic digestion process without pre-treatment. Air stripping pre-treatment will be conducted using an airflow rate of 4L/min for 1 to 4 days. The treated POME will be tested for its ammonia nitrogen content and the results of the parameter test before and after the air stripping pre-treatment process will be compared. After the pre-treatment process, POME will undergo anaerobic digestion for biogas production. A glass bottle containing treated POME will be connected with a nalophan bag. The process of anaerobic digestion will be taking place for 7days. The amount of biogas production trapped in the nalophan bag from the anaerobic digestion process will be measured using the water displacement method. From the results, the reduction of ammonia nitrogen of POME is reduced to 92.8% from 0.42 ml to 0.03 ml. The production of biogas resulted in 5.54 ml/h for the rate of wet biogas production while 5.23 ml/h was collected for the rate of dry biogas production. Even though stripping time 4 produces less biogas, the quality is higher compared to stripping time 1. This study also concludes that the higher the pH content along with longer stripping time, the ammonia nitrogen reduction will be high thus enhancing the production of biogas.